2009
DOI: 10.2320/matertrans.md200812
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mechanical Properties and Microstructures with Equivalent Strain in Pure Fe Processed by High Pressure Torsion

Abstract: Pure Fe (99.96%) was processed by high pressure torsion (HPT) using disc and ring samples. When the microhardness and tensile properties are plotted against the equivalent strain, the individual properties fall well on unique single curves, level off at the equivalent strain of $40. At the saturated level, the tensile strength of 1050 MPa and the elongation to failure of 2% are attained. Transmission electron microscopy showed that a subgrain structure containing dislocations develops at an initial stage of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
88
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 32 publications
12
88
2
Order By: Relevance
“…22) For the case of Fe and Ti after processing at 0.6 GPa, the equivalent strain of 80 appears to be insufficient to reach the steady state and it was confirmed that the hardness level was still lower even after N ¼ 20 corresponding to equivalent strain up to 370. Considering the fact that the applied pressure of 0.6 GPa is lower than the yield stresses of 1 GPa for Fe and 0.8 GPa for Ti obtained by tensile testing, 7,16) there may be a critical pressure, P C , near the yield stress, below which the increase in the hardness is very slow or may be constant with respect to the equivalent strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22) For the case of Fe and Ti after processing at 0.6 GPa, the equivalent strain of 80 appears to be insufficient to reach the steady state and it was confirmed that the hardness level was still lower even after N ¼ 20 corresponding to equivalent strain up to 370. Considering the fact that the applied pressure of 0.6 GPa is lower than the yield stresses of 1 GPa for Fe and 0.8 GPa for Ti obtained by tensile testing, 7,16) there may be a critical pressure, P C , near the yield stress, below which the increase in the hardness is very slow or may be constant with respect to the equivalent strain.…”
Section: Resultsmentioning
confidence: 99%
“…1 for (a) Au, (b) Cu, (c) Pt, (d) Ni, (e) Fe and (f) Ti samples processed under different pressures in the range of 0.6-6 GPa. Here, the equivalent strain was calculated using the equation as described earlier 7,16,19) where the effect of slippage and thickness reduction during HPT was taken into account. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) This should be mainly caused by quite different behavior of dislocations due to different stacking-fault energies (SFEs) for Al (166 mJ/m 2 ) and Cu (45 mJ/m 2 ). 4) Recently, the origin of the different SFEs has been explained by the different bonding nature.…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing number of turns, the microstructures usually evolve toward homogeneity and many metals exhibit a complete homogeneity at high numbers of turns. Materials showing this behavior include Al, [3,[8][9][10][11][12][13] Cu, [14][15][16] Ti, [17][18][19] Mg, [20][21][22][23] Fe, [24][25][26] Ni, [27,28] and numerous others metals and alloys. [29,30] Nevertheless, some materials show a different type of behavior when processed by HPT.…”
Section: Introductionmentioning
confidence: 99%